2011
DOI: 10.1007/s10863-011-9341-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tl+ on mitochondrial permeability transition pore in Ca2+-loaded rat liver mitochondria

Abstract: The Tl(+)-induced opening of the MPTP in Ca(2+)-loaded rat liver mitochondria energized by respiration on the substrates succinate or glutamate plus malate was recorded as increased swelling and dissipation of mitochondrial membrane potential as well as decreased state 4, or state 3, or 2,4-dinitrophenol-stimulated respiration. These effects of Tl(+) increased in nitrate media containing monovalent cations in the order of Li(+) < NH (4) (+) ≤ Na(+) < K(+). They were potentiated by inorganic phosphate and dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 51 publications
6
30
0
Order By: Relevance
“…La 3+ , RR and EGTA inhibited the increase in IMM permeability for acetyl-CoA in Ca 2+ loaded RLM [39]. We showed that the MPTP opening was markedly diminished in the presence of the MPTP inhibitors (ADP, CsA, Mg 2+ , and Li + ) [3]. With this as our background, our aim was to study the influence of bivalent metal ions (Sr 2+ , Ba 2+ , Mn 2+ , Co 2+ , and Ni 2+ ) as well as Y 3+ and La 3+ on the Tl + -induced MPTP opening in the inner membrane of CaRLM.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…La 3+ , RR and EGTA inhibited the increase in IMM permeability for acetyl-CoA in Ca 2+ loaded RLM [39]. We showed that the MPTP opening was markedly diminished in the presence of the MPTP inhibitors (ADP, CsA, Mg 2+ , and Li + ) [3]. With this as our background, our aim was to study the influence of bivalent metal ions (Sr 2+ , Ba 2+ , Mn 2+ , Co 2+ , and Ni 2+ ) as well as Y 3+ and La 3+ on the Tl + -induced MPTP opening in the inner membrane of CaRLM.…”
Section: Introductionmentioning
confidence: 67%
“…Wistar adult male rats (200-250 g) were used for liver mitochondria isolation according to the standard procedure [3]. Mitochondria were suspended in a buffer containing 250 mM sucrose, 3 mM Tris-HCl (pH 7.3), and 0.5 mM EGTA.…”
Section: Mitochondrial Isolationmentioning
confidence: 99%
See 3 more Smart Citations